Penerapan Supervisi Akademik Berbasis Coaching Pada Guru Pak di SMP Negei 1 Lolak Kabupaten Bolaang Mongondow - Lolowang, Yetty; Weol, Wolter; Mamahit, Meyke M. (Jurnal Ilmiah Wahana Pendidikan, 2024)
The purpose of this research was : 1. To apply coaching-based academic supervision to christian religious education teachers at SMP Negeri I Lolak, Bolaang Mongondow Regency, 2. To identify external and internal factors that support and hinder the implementation of coaching-based academic supervision for christian religious education teachers at SMP Negeri I Lolak, Bolaang Mongondow Regency, 3. to find the solutions to overcome obstacles in the implementation of coaching-based academic supervision for christian religious education teachers at SMP Negeri I Lolak, Bolaang Mongondow Regency. The research method used was descriptive qualitative with data collection techniques through observation, interview, and documentation study. The results of the study show that coaching-based academic supervision can improve the pedagogical and professional competence of christian religious education teachers at SMP Negeri I Lolak, Bolaang Mongondow Regency. The coaching process implemented includes lesson plan, execution, and evaluation conducted collaboratively between supervisors and teachers. Coaching also helps to identify and address challenges faced by teachers in the learning process. As a result, the motivation and performance of christian religious education teachers at SMP Negeri I Lolak, Bolaang Mongondow Regency teachers have significantly improved. Thus, the application of coaching-based academic supervision has proven effective in improving the quality of teaching at SMP Negeri I Lolak, Bolaang Mongondow Regency.